Outcomes after transaortic transcatheter aortic valve implantation: long-term findings from the European ROUTE. (20th October 2018) - Cocchieri, Riccardo; Petzina, Rainer; Romano, Mauro; Jagielak, Dariusz; Bonaros, Nikolaos; Aiello, Marco; Lapeze, Joel; Laine, Mika; Chocron, Sidney; Muir, Douglas; Eichinger, Walter; Thielmann, Matthias; et al.
Abstract: OBJECTIVES: There is lack of data regarding the longer-term outcomes of patients undergoing transaortic (TAo) transcatheter aortic valve implantation (TAVI). We aimed to provide a contemporary snapshot of the types and frequencies of events in the year following TAo-TAVI. METHODS: The Registry of the Utilization of the TAo-TAVI approach using the Edwards SAPIEN Valve (ROUTE) is a multicentre, European, prospective, observational registry of aortic stenosis patients undergoing TAo-TAVI. Patients were grouped according to the composite end point death, myocardial infarction, stroke/transient ischaemic attack, major vascular complications, life-threatening bleeding, acute kidney injury (AKI) and/or cardiovascular rehospitalization. RESULTS: Two hundred and fifty-three patients with a mean age of 81.5 ± 5.8 years were included, of whom 89 (35.2%) patients met the composite end point (the event group) and 164 (64.8%) patients did not (the event-free group). New York Heart Association (NYHA) class III/IV (85.2% vs 71.8%, P = 0.017), Canadian Cardiovascular Society angina class III/IV (22.6% vs 11.4%; P = 0.021), pulmonary disease (32.6% vs 18.9%; P = 0.015) and renal insufficiency (15.7% vs 3.0%; P < 0.001) were more common in the event group. At 1 year, the most common event was death (19.1%), followed by AKI stage II or III (14.7%). The baseline renal insufficiency was the strongest independent predictor of composite end point achievement [odds ratio (OR) 7.55, 95% confidence interval (CI) 2.33–24.56], followed by NYHA class III/IV (OR 2.316, 95% CI 1.06–5.06) and pulmonary disease (OR 2.91, 95% CI 1.45–5.85). Pulmonary disease was also an independent predictor of 1-year mortality (OR 3.01, 95% CI 1.34–6.75). CONCLUSIONS: Long-term outcomes after TAo-TAVI appear to be similar to those for TAVI via other non-transfemoral access routes. Awareness of characteristics associated with poorer outcomes may aid patient selection and identification of those requiring closer post-procedural monitoring. Clinical trial registration number: ClinicalTrials.gov identifier: NCT01991431.